Training Health Professional Students as Lay Counselors to Treat Depression in a Student-Run Free Clinic - Rodriguez Guzman, Juan; Ramos, Marco A; Silva, Michelle; Mata, Douglas A; Raila, Hanna; Rohrbaugh, Robert; Barkil-Oteo, Andres (Journal of Student-Run Clinics, 2018)
Background: Global initiatives to train lay counselors in mental health care delivery have been effective with depressed patients in low-income countries. However, lay-counselor models have not been employed to address mental health disparities in high-income countries (HICs). This article presents a lay-counselor program for providing mental health interventions to uninsured, undocumented immigrants in a low-resource setting in the United States. Methods: Mental health professionals trained students as lay counselors to deliver psychoeducation, reduction of psychosocial stressors, and behavioral activation interventions to Spanish-speaking, undocumented immigrants with symptomatic depression. Changes in depressive symptoms prior to and after participation in the program were assessed with the Patient Health Questionnaire-9 (PHQ-9). The educational component of the program was examined administering a survey to the lay counselors. Results: Twenty-five patients enrolled in the program, 68% female, mean age 39 years (standard deviation [SD] = 12). Eighteen patients completed the program. PHQ-9 data were available from 15 individuals, among whom the mean baseline score was 11.7 (SD = 6.2) and mean final score was 4.6 (SD = 4.2; p < 0.001). The survey showed that students had increased interest in both underserved populations and mental health after participation in the program. Conclusions: Lack of access to psychiatrists and psychologists is a growing problem for uninsured people suffering from depression in the United States. Lay counselor approaches may help to address mental health disparities in low-resource settings in HICs and may also be used to help recruit health professional students into the psychiatric profession.